2D-QSAR Analysis of Some Imidazole with Acylsulphonamides and Acylsulfamides as Selective AT1 Angiotensin-II Receptor Antagonistas a Hypertensive Agent - Jain, Anurekha; Gupta, V.B.; Jain, Avijeet; Gupta, Arun; Chaturvedi, S.C. (Asian Journal of Chemistry, 2010)
A series of angiotensin-II receptor antagonists of some imidazole with acylsulphonamides and acylsulfamides were subjected to 2D-QSAR analysis using Hansch analysis, by using a combination of thermodynamic, electronic and spatial descriptor. Several QSAR models were obtained using stepwise regression analysis. One model was selected on basis of the statistical values that shows better significance with biological activity. The best QSAR models were further validated by leave-one-out cross-validation method. The studies have helped to ascertain the role of different substituents in explaining the observed inhibitory activity of this analogue. From the study, it is predicted that hydrophobicity (π) at the X substitution and electronic parameter, resonance effect (r) at the R5 and hydrogen donor effect at the X and at the R5 substitution shows positive contribution to biological activity.